Analisis Kepadatan Penduduk, Pertumbuhan Ekonomi dan Anggaran Lingkungan terhadap Kualitas Lingkungan Hidup di Indonesia - Muhammad Agung Patra Yuda; Idris Idris (Universitas Negeri Padang, 2022)
Research aims to analyze the impact of population density, economic growth and environmental budget on environmental quality in Indonesia. The data used in this study is panel data from 2012 to 2019 covering 32 provinces in Indonesia, data obtained from BPS and KEMENLKH and the Ministry of the Environment. This research uses panel data regression analysis with Population Density, Economic Growth, and Environmental Budget as independent variables and Environmental Quality as the dependent variable. The results of this resaerch that the population density variable has a positive and insignificant effect on the quality of the environment in Indonesia, the variable of economic growth has a positive and significant effect on the quality of the environment in Indonesia. On the other hand, the environmental budget variable has a negative and insignificant effect on the quality of the environment in Indonesia.